K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
HM
0
H
15 tháng 7 2022
Vì a chia 4 dư 1 nên $a = 4m + 1(m ∈N)$
Vì b chia 4 dư 3 nên $b = 4n + 3 ( n ∈N)$
Ta có :
$(b - a)(b + a) = b^2 - a^2 = (4n + 3)^2 - (4m + 1)^2 = 16n^2 + 24n + 9 - 16m^2 - 8m - 1$
$= 16(n^2 - m^2) + 24n - 8m + 8$
Vì : $16(n^2 - m^2) ⋮ 4 ; 24n ⋮ 4 ; -8m ⋮ 4 ; 8 ⋮ 4$ nên $(b - a)(b + a) ⋮ 4$
NN
Nguyễn Ngọc Anh Minh
CTVHS
VIP
15 tháng 7 2022
a=4m+1; b=4n+3
(b-a)(b+a)=(4n+3-4m-1)(4n+3+4m+1)=
=[(4n-4m)+2].[(4n+4m)+4]=
=(4n-4m)(4n+4m)+4(4n-4m)+2(4n+4m)+8=
=16(n2-m2)+4(4n-4m)+8(n+m)+8 chia hết cho 4